How professionalisation of outreach practitioners could improve the quality of evaluation and evidence: a proposal. (3rd April 2022) - Clements, Naomi; Davies, Sara; Mountford-Zimdars, Anna
ABSTRACT: Professionalising outreach and evaluation work would enhance the quality and rigour of provision, benefit widening participation students and achieve regulatory requirements (Bowes et al. [2019]. The National Collaborative Outreach Programme End of Phase 1 report for the national formative and impact evaluations . Office for Students; Rainford [2020]. "Working with/in institutions: how policy enactment in widening participation is shaped through practitioners' experience." British Journal of Sociology of Education 42 (2): 287–303). This article presents practitioners' experiences of how social justice can often feel unaligned to the technical expertise required in rigorous project design and evaluation. Professionalising outreach would achieve both improved practice and meet practitioners' needs for development and a united professional voice. A professional body sharing standard methods of practice, offering CPD and skills would elevate outreach practitioners to a 'professional' standing (Eraut [1994]. Developing professional knowledge and competence . Falmer Press).